A study on drug utilization pattern of anticoagulants in post-cardiac surgeries at a tertiary care hospital - G. K., Priya; George, Blessy K.; Ramaiah, Balakeshawa; M., Ramya (International Journal of Basic & Clinical Pharmacology, 2023)
Background: The study is being carried out mainly to understand the prevention of coagulation of blood after a patient undergoing various types of cardiac surgeries, using different anticoagulation therapies suitable to particular types of cardiac surgery. This study was conducted to know the types of anticoagulants prescribed to patients who have undergone different types of cardiac surgeries along with the prescribed anticoagulants. Methods: The study method used was a retrospective and prospective observational study carried out on 50 patients who underwent cardiac surgeries in the department of cardiology and medicine. Results: A total of 50 patients were enrolled for this study who satisfied the inclusion criteria, out of which 64% of patients were males, and 36% were females. The highest number of patients were found to be in between the age group of 61-70 yrs (34%), whereas age group between 51-60 yrs (28%), age group 71 and above (18%), 41-50 (14%), 21-30 yrs (4%) and 18-20 yrs (2%) respectively. Most of the patients had undergone Coronary Artery bypass grafting. It was seen that the highest Anticoagulant being prescribed was Heparin in most of the post-cardiac surgeries. Whereas drugs like dalteparin, acenocoumarol, and warfarin were prescribed the majority in valvular heart surgeries. Conclusions: Various cardiac surgeries were taken into consideration for the study. The most common anticoagulants prescribed were heparin, dalteparin, acenocoumarol, and warfarin in coronary artery bypass surgery and valvular heart surgeries respectively.